Strategi Transformasi Pembelajaran Nilai-Nilai Aswaja: Dari Teori ke Praktik Sehari-Hari dalam Membangun Karakter Siswa MI - Dewi Niswatul Fithriyah; Luluk Nurul Aini; Nur Diana Rahayu; Shafira Aulia Agustin; Hafni Zukhrufina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Value-based education of Ahlussunnah Wal Jama’ah (Aswaja) plays an important role in shaping the personality of students in elementary schools. This article aims to analyze the strategies for transforming Aswaja values from the theoretical realm to practical application in the daily lives of students. The method used in writing this article is literature review based on information from the internet, including scientific articles, books, and other trusted sources. The results of the study show that strategies for transforming Aswaja values can be applied through several main approaches, namely structured regular worship habits, reflective teaching approaches, parental involvement as primary support, integration of Aswaja values in social and religious activities, value-based learning of Aswaja, and the exemplary behavior of teachers as role models. These strategies are effective in internalizing Aswaja values in students, marked by an increase in spiritual awareness, disciplined attitudes, social concern, and student tolerance. With the implementation of this strategy, students not only understand the values of Aswaja theoretically but also are able to practice them in their daily lives. This article is hoped to serve as a reference for educators in developing character education programs based on Aswaja values in elementary schools.